Eutrophication Conditions in Two High Mountain Lakes: The Influence of Climate Conditions and Environmental Pollution - Fátima Goretti García-Miranda; Claudia Muro; Yolanda Alvarado; José Luis Expósito-Castillo; Héctor Víctor Cabadas-Báez (Hydrology)
The lakes known as El Sol and La Luna are high mountain water deposits located in Mexico within an inactive volcanic system. These lakes are of ecological importance because they are unique in Mexico. However, currently, the lakes have experienced changes in their shape and an increase in algae blooms, coupled with the degradation of the basin, which has alerted government entities to the need to address the lakes’ problems. To address the environmental status of El Sol and La Luna, a trophic study was conducted during the period of 2021–2023, including an analysis of the influence of climatic variables, lake water quality, and eutrophication conditions. The trophic state was established based on the eutrophication index. The Pearson correlations defined the eutrophication interrelation between the distinct factors influencing the lakes’ status. El Sol registered higher eutrophication conditions than La Luna. El Sol was identified as seasonal eutrophic and La Luna as transitioning from oligotrophic to mesotrophic, showing high levels of chlorophyll, total phosphorus, and total nitrogen and low water transparency. The principal factors altering the eutrophic conditions were water pollution and climatic variables (precipitation and ambient temperature). Eutrophication was the prime factor impacting perimeter loss at El Sol, whereas at La Luna, it was due to a decline in precipitation.